Commercial Policy Under Fixed and Flexible Exchange Rates - Tower, Edward (Quarterly Journal of Economics, 1973)
I. Is devaluation deflationary? 437. — II. The Keynesian model, 442. — III. Commercial policy under fixed rates, 446. — IV. Commercial policy under flexible rates, 449. — V. The terms-of-trade effect can be zero or negative, 452. — VI. Concluding remarks, 453.